2019
DOI: 10.1002/jgt.22507
|View full text |Cite
|
Sign up to set email alerts
|

Normal edge‐colorings of cubic graphs

Abstract: A normal k‐edge‐coloring of a cubic graph is a proper edge‐coloring with k colors having the additional property that when looking at the set of colors assigned to any edge e and the four edges adjacent to it, we have either exactly five distinct colors or exactly three distinct colors. We denote by χ N true′ ( G ) the smallest k, for which G admits a normal k‐edge‐coloring. Normal k‐edge‐colorings were introduced by Jaeger to study his well‐known Petersen Coloring Conjecture. More precisely, it is kno… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…Every nowhere-zero Z 3 2 -flow φ can be seen as a normal 7-edge-coloring of C(n, p) (see Theorem 5 in [17]). Moreover, the first entry of the flow on edges of M is 0, and the first entry of the flow on edges outside M is 1.…”
Section: Permutation Snarksmentioning
confidence: 99%
See 3 more Smart Citations
“…Every nowhere-zero Z 3 2 -flow φ can be seen as a normal 7-edge-coloring of C(n, p) (see Theorem 5 in [17]). Moreover, the first entry of the flow on edges of M is 0, and the first entry of the flow on edges outside M is 1.…”
Section: Permutation Snarksmentioning
confidence: 99%
“…The main result of [17] states that any simple cubic graph admits a normal 7-edgecoloring. There it is also shown that any bridgeless cubic graph G admits a normal 7-edgecoloring (see also [3]), and this result is obtained simply by considering a nowhere zero Z 3 2 -flow of G. One may wonder whether we can choose the nowhere zero Z 3 2 -flow θ of G, such that for one nonzero element γ ∈ Z 3 2 , we have θ −1 (γ) = ∅.…”
Section: Future Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Observe that not all cubic graphs admit a normal k-edge-coloring for some k. An example of such a graph is the graph from Figure 2. On the positive side, all simple cubic graphs admit a normal 7edge-coloring [10]. The smallest k (if it exists) for which a cubic graph G admits a normal k-edge-coloring is called a normal chromatic index of G and is denoted by χ N (G).…”
Section: Introductionmentioning
confidence: 99%